Health related quality of life in survivors of pneumococcal meningitis. - Legood, R; Coen, P; Knox, K; Viner, R; El Bashir, H; Christie, D; Patel, B; Booy, R (2009)
AIM: To estimate the overall long-term health related quality of life implications of an episode of pneumococcal meningitis in childhood. METHOD: Cases were identified through two regional UK surveillance studies and traced via their general practitioners (GPs) or local hospital paediatrician. Siblings were used as controls where available. Health related quality of life was assessed using the health utilities index (HUI). Mean utility scores were compared between cases and controls and univariate linear regression was used to identify factors that influenced the overall utility scores. RESULTS: HUI data were available for 71 cases and 66 controls. The mean overall utility score for cases 0.774 (95% CI 0.711- 0.837) was significantly lower than for controls 0.866 (95% CI 0.824-0.907) (p-value = 0.0185). Hearing was the most significantly affected health attribute (p-value < 0.006). In cases, males had lower quality of life scores than females (p-value = 0.018), however this was not seen in controls. CONCLUSION: An episode of pneumococcal meningitis results in a long-term decrement in overall health related quality of life and is significantly related to hearing loss.